On the variation of regional CO2 exchange over temperate and boreal North America. Issue 4 (1st October 2013) - Zhang, Xia; Gurney, Kevin R.; Peylin, Philippe; Chevallier, Frédéric; Law, Rachel M.; Patra, Prabir K.; Rayner, Peter J.; Röedenbeck, Christian; Krol, Maarten
Abstract [1] Inverse‐estimated net carbon exchange time series spanning two decades for six North American regions are analyzed to examine long‐term trends and relationships to temperature and precipitation variations. Results reveal intensification of carbon uptake in eastern boreal North America (0.1 PgC/decade) and the Midwest United States (0.08 PgC/decade). Seasonal cross‐correlation analysis shows a significant relationship between net carbon exchange and temperature/precipitation anomalies during the western United States growing season with warmer, dryer conditions leading reduced carbon uptake. This relationship is consistent with "global change‐type drought" dynamics which drive increased vegetation mortality, increases in dry woody material, and increased wildfire occurrence. This finding supports the contention that future climate change may increase carbon loss in this region. Similarly, higher temperatures and reduced precipitation are accompanied by decreased net carbon uptake in the Midwestern United States toward the end of the growing season. Additionally, intensified net carbon uptake during the eastern boreal North America growing season is led by increased precipitation anomalies in the previous year, suggesting the influence of "climate memory" carried by regional snowmelt water. The two regions of boreal North America exhibit opposing seasonal carbon‐temperature relationships with the eastern half experiencing a net carbon loss with near coincident increases in temperature and the western half showing increased net carbon uptake. The carbon response in the boreal west region lags the temperature anomalies by roughly 6 months. This opposing carbon‐temperature relationship in boreal North America may be a combination of different dominant vegetation types, the amount and timing of snowfall, and temperature anomaly differences across boreal North America.